2021
DOI: 10.24083/apjhm.v16i4.1139
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Adequacy among Haemodialysis Patients in Eastern Mediterranean Region: A Systematic Review and Meta-Analysis

Abstract: Introduction: Dialysis adequacy is one of the most important indicators for measuring the quality of care provided in hemodialysis (HD) wards. Despite individual studies, there is still no comprehensive study about dialysis adequacy in the Eastern Mediterranean Region (EMRO). This study was conducted to evaluate the dialysis adequacy in HD patients in the EMRO. Methods: In the present systematic review and meta-analysis international (EMBASE, Scopus, PubMed, Web of Science) and national (SID, MAGIRAN) databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
(28 reference statements)
0
0
0
Order By: Relevance
“…CKD patients in this study received good service from the dialysis center as indicated by the URR value of 65%, where the standard for dialysis adequacy using the URR formula was 65% even during the COVID-19 pandemic. The mean URR in Indonesia is better than the country in Eastern Mediterranean region (Ebadi et al, 2021). The not to high anxiety level allows good dialysis adequacy condition.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…CKD patients in this study received good service from the dialysis center as indicated by the URR value of 65%, where the standard for dialysis adequacy using the URR formula was 65% even during the COVID-19 pandemic. The mean URR in Indonesia is better than the country in Eastern Mediterranean region (Ebadi et al, 2021). The not to high anxiety level allows good dialysis adequacy condition.…”
Section: Discussionmentioning
confidence: 90%
“…Dialysis can be performed by patients at a dialysis center in a hospital (T. Lee et al, 2021). Dialysis adequacy is one of the most important indicators for measuring the quality of care provided in HD wards (Ebadi et al, 2021). Adequate dialysis provides information about the adequacy of the dialysis dose received by the patient to obtain adequate results, namely the removal of toxins and waste products from the patient (Dehvan et al, 2018;Somji et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation